1992
DOI: 10.1093/carcin/13.11.1989
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of human DNA repair protein N-methylpurine-DNA glycosylase results in the increased removal of N-methylpurines in DNA without a concomitant increase in resistance to alkylating agents in Chinese hamster ovary cells

Abstract: N-Alkylpurines induced in DNA by simple monofunctional alkylating agents are known to be cytotoxic and possibly indirectly mutagenic. These adducts are removed by the ubiquitous N-methylpurine-DNA glycosylase (MPG) in a multistep repair pathway. Chinese hamster ovary (CHO) cell clones expressing 2- to 16-fold enhanced levels of MPG activity were isolated from cells stably transfected with human MPG cDNA expression plasmids. The in vivo removal of 3-methyladenine and 7-methylguanine from some of these lines was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 0 publications
5
33
0
Order By: Relevance
“…Overexpression of methyl-specific DNA glycosylases has been reported to have varying effects in mammalian cells, ranging from no effect to eliciting an increase in or a decrease in sensitivity to alkylating agents (Ibeanu et al, 1992;Klungland et al, 1992;Habraken and Laval, 1993). We and Table 1) or with media for 6, 12, 24, and 48 h. These cells were also treated with 15 M ETO or media for 24 h. After drug treatment, the cell pellet was resuspended in 1ϫ cell lysis buffer, and cytosolic extract was used for the assay of caspase-3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of methyl-specific DNA glycosylases has been reported to have varying effects in mammalian cells, ranging from no effect to eliciting an increase in or a decrease in sensitivity to alkylating agents (Ibeanu et al, 1992;Klungland et al, 1992;Habraken and Laval, 1993). We and Table 1) or with media for 6, 12, 24, and 48 h. These cells were also treated with 15 M ETO or media for 24 h. After drug treatment, the cell pellet was resuspended in 1ϫ cell lysis buffer, and cytosolic extract was used for the assay of caspase-3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in yeast, when BER is imbalanced by an excess of abasic sites (generated by over-expression N-methylpurine-DNA glycosylases, MPG), the rate of spontaneous mutation is increased signi®cantly (Chakravarti et al, 1991;Berdal et al, 1998;Glassner et al, 1998;Lau et al, 2000). Chinese hamster ovary cells over-expressing human MPG (a broad spectrum glycosylase), however, when exposed to methylating agents, did not show increased mutagenesis but showed inhibition of DNA synthesis, chromosomal aberrations and DNA breaks (Ibeanu et al, 1992;Coquerelle et al, 1995). On the other hand, Chinese hamster V79 cells over-expressing bacterial tag gene (removes only 3-methyladenine) were more resistant to cytotoxic and mutagenic e ects of methylating agents (Klugland et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme's precise role in protecting cells from the cytotoxic effects of alkylating agents is still controversial (Klungland et al, 1992;Habraken and Laval, 1993;Imperatori et al, 1994;Ibeanu et al, 1992;Matijasevic et al, 1993). Klungland et al (1992 reported that V79 hamster lung fibroblasts and murine haematopoietic cells permanently expressing the tag gene showed increased resistance to killing by methylmethanesulphonate (MMS) and methylnitrosurea (MNU).…”
mentioning
confidence: 99%